Satisfaction in hospitality on TripAdvisor.com: An analysis of the correlation between evaluation criteria and overall satisfaction - Limberger,Pablo Flôres (2014)
Social media has changed the way tourists seek and exchange information, resulting in changes in the management of tourism businesses including hospitality facilities. Guest reviews and comments have had an impact on the reputation of organisations, both positive and negative. Websites with user-generated content spread this information to other tourists through the evaluation of service provided and thereby influence the decision of new visitors. Accordingly, this research sought to identify the correlation between overall satisfaction and the evaluation criteria used on a website. For this, we analysed 660 reviews (236 of three-star hotels, 125 of four-star hotels and 299 of five-star hotels) on TripAdvisor, containing independent reviews including overall satisfaction, value (cost-benefit), location, sleep quality, rooms, cleanliness and service. Results showed a strong correlation of overall satisfaction with the criteria of room, service provided and cost-benefit.